Picture books for initial EFL literacy and rights recognition. (2023)
The present investigation aimed to establish how the design of picture books can aid in the development of initial literacy skills for EFL learners while fostering their recognition as subjects of rights. The study was conceived from a qualitative point of view using Action Research as the research method and it was applied to 5th grade students from Magdalena Ortega de Nariño public school. The researcher used Project-Based Learning as the pedagogical approach and the Educación para la Paz framework as the guideline to build the content since the topics treated are related to the Colombian internal conflict. Axel Honneth’s recognition theory was the theoretical standpoint taken to support the students’ development regarding the concept of recognition that crosses the document. Including diagnostic sessions, the study was applied in 9 sessions and the final product was socialized in a school forum. The findings showed an improvement in the children’s literacy skills and meaning construction capacity; they also showed a greater awareness and recognition of their own rights and respect for other’s rights.